2006
DOI: 10.1158/0008-5472.can-05-3092
|View full text |Cite
|
Sign up to set email alerts
|

Functional Coupling of p38-Induced Up-regulation of BiP and Activation of RNA-Dependent Protein Kinase–Like Endoplasmic Reticulum Kinase to Drug Resistance of Dormant Carcinoma Cells

Abstract: It has been proposed that occult, disseminated metastatic cells are refractory to chemotherapy due to lack of proliferation. We have shown that p38 activation induces dormancy of squamous carcinoma cells. We now show that p38 signaling in these cells activates a prosurvival mechanism via the upregulation of the endoplasmic reticulum (ER) chaperone BiP and increased activation of the ER stress-activated eukaryotic translation initiator factor 2A kinase RNA-dependent protein kinase-like ER kinase (PERK) allowing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
294
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(309 citation statements)
references
References 49 publications
10
294
0
Order By: Relevance
“…42 Moreover, it has also been reported that active p38 in cancer cells is able to induce an ER stress response to coordinate cell survival through the activation of PERK and IRE-1. 43 To evaluate the potential role of p38-mediated induction of chronic ER stress in BRAF mutant melanoma cells, we first compared the expression of activated p38 (P-p38) in CHL-1 and A375 cells, demonstrating increased P-p38 levels in BRAF mutated compared with BRAF wt cells (Figure 7a, upper panel), also confirmed in our cohort of melanoma cell lines (Supplementary Figure S4 A and B). To unveil the impact of constitutively activated p38 on melanoma basal autophagy, we inhibited the activity of p38 by ectopic expression of a p38 dominant negative (p38-DN) into A375 cells prior to evaluating Figure 5 JNK and basal autophagy.…”
Section: Sk-mel-110 Sk-mel-110mentioning
confidence: 66%
“…42 Moreover, it has also been reported that active p38 in cancer cells is able to induce an ER stress response to coordinate cell survival through the activation of PERK and IRE-1. 43 To evaluate the potential role of p38-mediated induction of chronic ER stress in BRAF mutant melanoma cells, we first compared the expression of activated p38 (P-p38) in CHL-1 and A375 cells, demonstrating increased P-p38 levels in BRAF mutated compared with BRAF wt cells (Figure 7a, upper panel), also confirmed in our cohort of melanoma cell lines (Supplementary Figure S4 A and B). To unveil the impact of constitutively activated p38 on melanoma basal autophagy, we inhibited the activity of p38 by ectopic expression of a p38 dominant negative (p38-DN) into A375 cells prior to evaluating Figure 5 JNK and basal autophagy.…”
Section: Sk-mel-110 Sk-mel-110mentioning
confidence: 66%
“…Inhibition of β1 integrin activity prevents tumor cell proliferation, but not cell viability, leading to the induction of a dormant state [42,43]. Further studies indicate that dormancy is mediated downstream of β1 integrin through decreases in FAK and MAPK signaling and activation of p38 and eIF2α [42,44,45]. Although it remains unclear if these mechanisms regulate dormancy in patients, it is proposed that dormancy is induced in disseminated tumor cells exposed to untoward microenvironments that do not facilitate proper ECM-integrin engagement.…”
Section: Detachment-induced Autophagy and Tumor Cell Dormancymentioning
confidence: 99%
“…The data implicating the UPR in tumor progression and hypoxia tolerance describe an important adaptive mechanism that cells in established tumors use to survive the tumor microenvironment. Furthermore, the PERKeIF2a pathway has been reported to be critical for tumor cell dormancy (133), an important clinical phenomenon, which also contributes to chemoresistance. However, the reliance of hypoxic and dormant tumor cells on a functional UPR may provide a unique therapeutic opportunity.…”
Section: Potential For Therapymentioning
confidence: 99%